Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Kooperatif Tipe STAD pada Materi Operasi Hitung Campuran Bilangan Bulat di SDK Weepangali - Wohangara, Ayub Umbu Tonga; Kaleka, Yohanis Umbu; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The research aims to describe the results of research on improving student learning outcomes through the Stad type cooperative learning model on the material on mixed whole number arithmetic operations in class VI SDK Weepangali. This research uses the classroom action research (PTK) method, with a stad type cooperative learning model, and includes two cycles, namely planning, implementation, observation, and reflection. Data collection techniques are observation, tests, and documentation. The research location was at SDK Weepangali, the research subjects were 31 class VI students. The results of this research show an increase in student learning outcomes after applying the STAD type cooperative learning model to the material on mixed integer arithmetic operations. The increase in student learning outcomes can be seen from the results of this research, classical completeness before conducting the research was 49.19%, in cycle I the percentage increased to 51% and cycle II increased to 74%. Based on the results of this research, the researcher concluded that the STAD type cooperative learning model can improve student learning outcomes in the material on mixed integer arithmetic operations in class VI SDK Weepangali